Concordance of Hormone Receptor Status and BRCA1/2 Mutation Among Women With Synchronous Bilateral Breast Cancer - Huang, Liang; Liu, Qi; Lang, Guan-Tian; Cao, A-Yong; Shao, Zhi-Ming (Frontiers in Oncology, 2020)
Abstract: Goals: BRCA1/2 mutations are associated with bilateral breast cancer. The extent of concordance between synchronous bilateral breast cancer (SBBC) tumors with respect to hormone receptor expression and BRCA1/2 mutations is unknown. We investigated the distribution of BRCA1/2 mutations and bilateral estrogen receptor (ER) status in SBBC. Methods: A retrospective analysis was performed on 15337 patients with primary breast cancer who underwent surgical treatment at the Fudan University Shanghai Cancer Center between 2007 and 2014. We included 163 patients with synchronous bilateral breast cancer who had germline BRCA1/2 mutations testing. BRCA1/2 pathogenic/likely pathogenic mutations and other clinicopathological characteristics were studied in further analyses. Results: Patients with SBBC developed breast cancer at an older age and had a higher rate of ER positivity than patients with UBC (p<0.001, separately). In contrast, 14.1% of SBBC patients had carcinomas with a lobular component in either breast based on pathological reports (p<0.001). Twelve patients had BRCA1 mutations, and 14 patients had BRCA2 mutations, while no patients had mutations in both genes. The BRCA1/2 mutation rate was higher in younger patients (23.4% vs. 11.1%, p=0.036). SBBC patients with a family history of breast cancer or bilateral ER-negative disease had a higher frequency of BRCA1/2 mutations than the cohort without a history of these conditions. SBBC with a bilateral ER-discordant status had a very low frequency of BRCA1/2 mutations (5.6%). Patients with an ER-positive (concordant or discordant) status had better 3-year disease-free survival than patients with a concordant ER-negative status (HR=0.324, 95% CI: 0.126-0.837, P=0.020). However, the outcomes were similar during long-term follow-up. Pathological lymph node stage was the only prognostic factor for SBBC in both univariate and multivariate Cox analyses. Conclusions: Our study shows that Chinese women with SBBC have different characteristics from their UBC counterparts. SBBC patients with a younger age, family history of breast cancer or bilateral ER-negative disease are more likely to have BRCA1/2 mutations. SBBC patients with a concordant ER-negative status had worse early outcomes. Our results suggest that there may be additional factors underlying the tumor biology and genetics of SBBC.